The Influence of Content Marketing on Instagram on Online Purchase Decisions for MsGlow Products with Purchase Intention as an Intervening Variable - Sriyanti Rahayu Pabebang; Jessy Yunus Dannari (CV. Publikasi Indonesia, 2024)
This research aims to examine the effect of Content Marketing on Instagram on purchasing decisions for Ms Glow products online, with Purchase Intention as an intermediary variable. The approach used in this research is quantitative with an explanatory research design. The population targeted by this study are Instagram users who have purchased Ms Glow products online or often shop at the MS Glow Makassar distributor store. The sample used consisted of 120 respondents, who were selected using the Maximum Likelihood Estimation (MLE) method. Several tests were conducted to ensure data validity and classical assumptions required in the analysis, which finally used path analysis to see the relationship between variables. The results of this study show that content marketing on Instagram has a strong and significant influence on purchasing decisions, both directly and through increasing purchase intention.